2001
DOI: 10.1002/eat.1041
|View full text |Cite
|
Sign up to set email alerts
|

The role of daily hassles in binge eating

Abstract: Theoretical and clinical implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 14 publications
6
80
0
2
Order By: Relevance
“…During periods of self-reported high stress, individuals show an increase in total calories consumed, total fat, saturated fat, and percent of calories from fat (McCann et al, 1990) compared to their intake during self-reported low stress times. These findings hold true in both naturalistic (Crowther, Sanftner, Bonafazi, & Shepard, 2001) and laboratory (Zellner et al, 2006) settings. Sweet and salty foods, as well as foods high in both fat and calories, are among the food types often preferred by binge eaters (Marcus, Wing, & Hopkins, 1988).…”
Section: Type Of Foodsupporting
confidence: 52%
“…During periods of self-reported high stress, individuals show an increase in total calories consumed, total fat, saturated fat, and percent of calories from fat (McCann et al, 1990) compared to their intake during self-reported low stress times. These findings hold true in both naturalistic (Crowther, Sanftner, Bonafazi, & Shepard, 2001) and laboratory (Zellner et al, 2006) settings. Sweet and salty foods, as well as foods high in both fat and calories, are among the food types often preferred by binge eaters (Marcus, Wing, & Hopkins, 1988).…”
Section: Type Of Foodsupporting
confidence: 52%
“…We also found that perceived time influenced participants' perceived hunger, which is highly related to sugar consumption (22). Stress levels can also be affected by perceived hunger (23), so future studies should address potential mediating effects of hunger-related hormones (e.g., ghrelin, peptide tyrosine-tyrosine) on the relation between perceived time and BGLs.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, dieting periods are common in the histories of binge eaters, although hunger itself does not appear to be enough to induce BE in the absence of stress and negative affective state (Polivy et al, 1994;Waters et al, 2001). Considerable evidence suggests that BE may be caused by a unique interaction between dieting and stress; thus, environmental stress and a history of cyclic food restrictions may be responsible for its precipitation and maintenance (Stice et al, 2001;Crowther et al, 2001;Wolff et al, 2000). Accordingly, recurring food restrictions are consistently the strongest predictor of overeating in response to stress (Wardle et al, 2000).…”
Section: Discussionmentioning
confidence: 99%